Artificial oral fluid characterisation: Potential for use as a reference matrix in drug testing. Issue 3 (18th October 2020) - Gavrilović, Ivana; Musenga, Alessandro; Cowan, David; Woffendin, Alison; Smart, Andrew; Gong, Fan; Harding, Duncan; Wolff, Kim
Abstract: Quality assurance schemes for drug‐screening programmes require access to large quantities of biological matrices for reference or control samples. This presents problems when the availability of a matrix, such as oral fluid (OF) for screening or for confirmatory purposes, limits the collection of large volumes. In such cases, synthetic alternatives of OF may provide a solution. The preparation of an artificial (synthetic) oral fluid (AOF) was conducted by dissolving its components (salts, surfactant, antimicrobial agent and mucin) in water. We characterised the physical properties of AOF to determine its suitability as a matrix for quality assurance purposes. The evaluation of pH, specific gravity (SG), conductivity (mS cm −1 ), freezing point depression (°C), light‐scattering and kinematic viscosity (mm 2 s −1 ) showed AOF to be a stable, reliable matrix. Synthetic OF was prepared using components (mucin, surfactants and so on) obtained from different suppliers and a comparison was performed. Our results suggest that AOF is a feasible matrix for the preparation of quality assurance samples for confirmatory or drug screening programmes. Abstract : Drug‐screening programmes require access to large quantities of biological matrices for reference or control samples. Characterisation of the physical properties, (including freezing point depression, light‐scattering and kinematic viscosity), of an artificial (synthetic) oral fluid suggest that this is a feasible matrix for the preparation of quality assurance samples for confirmatory or drug screening programmes, thus providing an alternative to invasive or complex sample collection procedures.